HUMERORADIAL STABILIZATION WITH SCREWS AND BRAIDED POLYESTER IN DOG WITH TRAUMATIC ELBOW LUXATION - Leal, Leonardo Martins; Magalhães, Carla Nazaré; Vasques, Gabriela Maria Benedetti; Terezan, Diécila Milena; Ciboldi, Thalissa Fernanda; Lavelli, Danielli Aparecida (Uningá Review, 2020)
The objective was to describe the case of a dog with traumatic elbow luxation that obtained good results after orthopedic correction with screws and braided polyester in a figure of "8". The owner reported that the animal escaped from his home and returned after 3 days without supporting the left thoracic limb. The patient was referred to the Uningá Veterinary Clinic 12 days after his return. In the clinical evaluation, it was possible to observe lameness without the support of the left thoracic limb, pain, crackling and instability of the elbow joint with lateral displacement of the radial head and olecranon in relation to the distal humerus. The diagnosis of lateral elbow luxation was confirmed by radiographic examination. The patient underwent orthopedic surgery and return 15 days after the surgical procedure with good wound healing and slight limping of the operated limb. After 90 days postoperatively, the patient had good walking, without clinical signs of lameness, pain, instability, and crackling of the operated limb. It was concluded with this report that the use of screws associated with the polyester braided in a figure of "8" can be a good option in the treatment of traumatic elbow dislocation.